SINERGI PERTANIAN DENGAN PARIWISATA DI BALI - Suryawan Wiranatha, A.A.P. Agung (Agrotekno, 2012)
Agriculture and tourism sector have been a priority in the policy of economy development of Bali. This policy is expected to bring a balance growth to the various economy sectors in Bali. However, tourism development in some agricultural areas leads to a decreasing of agriculture sector in these areas. It is caused by some reasonsm namely: the changed of land use from agriculture land to tourism facilities, the use of irrigation water for tourist facilities, and the lack of employees in agriculture sector. Theoretically, a growth in one economy sector will pull another economy sector because they are closely linked through supply-demand mechanism. Linkages between agriculture and tourism sector could be achieved through several activities, such as: (i) agricultural landscaoe as a tourist attraction (sight seeing); (ii) agricultural activities, including agroindustry as tourist attractions (agrotourism); (iii) agricultural products supplied for hotel and restaurants (agrobussiness). A successful effort in facilitating linkages between agriculture and tourism sectors could be able to empower agriculture sector in Bali, and could minimize land use changes from agriculture land to other land uses in Bali. Thereforem agriculture practices in Bali will be still exist, and available as tourist attractions.
Keywords: Agriculture, tourism, Bali